Synthesis, Characterization, and Biological Evaluation of Meldrum's Acid Derivatives: Dual Activity and Molecular Docking Study - Syed Nasir Abbas Bukhari; Mohamed Abdelwahab Abdelgawad; Naveed Ahmed; Muhammad Wahab Amjad; Muhammad Ajaz Hussain; Mervat A. Elsherif; Hasan Ejaz; Nasser H. Alotaibi; Ignjat Filipović; Nenad Janković (MDPI AG, 2023)
In the presented study, eight novel Meldrum's acid derivatives containing various vanillic groups were synthesized. Vanillidene Meldrum's acid compounds were tested against different cancer cell lines and microbes. Out of nine, three showed very good biological activity against E. coli, and HeLa and A549 cell lines. It is shown that the O-alkyl substituted derivatives possessed better antimicrobial and anticancer activities in comparison with the O-acyl ones. The decyl substituted molecule (3i) has the highest activity against E. coli (MIC = 12.4 μM) and cancer cell lines (HeLa, A549, and LS174 = 15.7, 21.8, and 30.5 μM, respectively). The selectivity index of 3i is 4.8 (HeLa). The molecular docking study indicates that compound 3i showed good binding affinity to DNA, E. coli Gyrase B, and topoisomerase II beta. The covalent docking showed that 3i was a Michael acceptor for the nucleophiles Lys and Ser. The best Eb was noted for the topoisomerase II beta-LYS482-3i cluster.